Introducing feminist theology - Clifford, Anne M (Maryknoll, N.Y. Orbis Books, 2001)
Introducing Feminist Theology responds to the questions What is feminist theology? and Why is it important? by considering the perspectives of women from around the globe who have very diverse life experience and relationships to God, Church and creation. Clifford introduces the major forms of feminist theology: radical, reformist, and reconstructionist, and highlights some of their specific characteristics.
Keywords: Feminist theology. Feministische theologie